Spatial and temporal root activity distribution in papaya (Carica papaya) determined by isotopic technique - KOTUR, S C; KESHAVA MURTHY, S V (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during 1999 to study spatial and temporal distribution of root activity in ’Surya’ papaya (Carica papaya L.). a hybrid, using 32 P soil-injection technique. The crop was raised all loamy sand soil (Typic Haplustalt) belonging to Thymugondlu series. During the carly vegetative and flowering stage (2-6 months after planting) the active roots grew up tn 60 cm radial distance aod 30 cm depth. of these, 75.2-91.6 % occurrud up to 40 cm distance. while 54.3-79.3% were found up to 15 cm depth. During the carly fruiting stage (7-10 months after planting). the roots further extended to 100 cm distance und 45 cm depth but bulk of the roots (marc than 70%) stilt remained within 60 cm distance and 30 cm depth. During the peak fruiting slage (11-14 months after planting), the root activity spread uniformly throughout the soil volume of 100 cm distance and 45 cm depth. The textural horizon (Bt) at.20 cm depth and below did not hamper rool grpwth, as the soil was kept moist throughout by rainfall or irrigation.